2000
DOI: 10.1002/1096-8628(20001218)95:5<482::aid-ajmg14>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the autosomal recessive (AR) craniometaphyseal dysplasia locus to chromosome region 6q21-22 and confirmation of genetic heterogeneity for mild AR spondylocostal dysplasia

Abstract: We report on a four-generation inbred family including 10 individuals affected with a form of craniotubular dysplasia (CTD). All affected patients were born to consanguineous healthy parents; this finding, together with the equal sex ratio among affected individuals and the occurrence of only normal individuals among their offspring, indicates that the disease in this family is an autosomal recessive (AR) trait. Taking into account the segregation pattern of the disease in the family and the radiological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The human chromosomal region that is homologous to the jc minimal genetic interval is present at 6q21. Craniometaphyseal dysplasia (OMIM 218400), which is a recessive syndrome characterized by cranial deformities including hearing loss, is among several human conditions that have been linked to the 6q21 region (Iughetti et al, 2000). However marker D6S302, which defines the centromeric border of the linked interval, is located 4 Mb telomeric to the recombinant jc marker D10Ntra118 excluding this syndrome as the human jc disease homolog.…”
Section: High-resolution Genetic Map Of Jcmentioning
confidence: 99%
“…The human chromosomal region that is homologous to the jc minimal genetic interval is present at 6q21. Craniometaphyseal dysplasia (OMIM 218400), which is a recessive syndrome characterized by cranial deformities including hearing loss, is among several human conditions that have been linked to the 6q21 region (Iughetti et al, 2000). However marker D6S302, which defines the centromeric border of the linked interval, is located 4 Mb telomeric to the recombinant jc marker D10Ntra118 excluding this syndrome as the human jc disease homolog.…”
Section: High-resolution Genetic Map Of Jcmentioning
confidence: 99%
“…Besides the initially described severe recessive form, a milder autosomal dominant form has been recognized [42]. In the recessive form the involvement of the diaphyses is more pronounced and craniometadiaphyseal dysplasia would have been more precise nomenclature [43]. Genetic linkage studies localized the gene for the recessive form to chromosome 6q21-22 whereas the dominant form maps to chromosome 5p15.2-p14.2 [43,44].…”
Section: Conditions With Increased Bone Density With Metaphyseal Invomentioning
confidence: 99%
“…In the recessive form the involvement of the diaphyses is more pronounced and craniometadiaphyseal dysplasia would have been more precise nomenclature [43]. Genetic linkage studies localized the gene for the recessive form to chromosome 6q21-22 whereas the dominant form maps to chromosome 5p15.2-p14.2 [43,44]. Recently the ANK gene was proven to underly the dominant form [45,46].…”
Section: Conditions With Increased Bone Density With Metaphyseal Invomentioning
confidence: 99%
“…Some pedigrees suggest an autosomal recessive (AR) mode of transmission [1,18,19,20,21] and a linkage study has identified a potential locus for the autosomal recessive form of CMD within a 7 cM interval on chromosome 6q21-22 [18]. However, a causative variant responsible for AR CMD could not be identified.…”
Section: Introductionmentioning
confidence: 99%